Analysis of Brand Credibility and Brand Reputation on Brand Performance - Saputri, Rara Zulia; Putra, Muhammad Farrel Risyawal; Yuliana, Lingga (SEAN Institute, 2024)
Leveraging the iPhone brand as a case study, the purpose of this research is to examine the impact of brand credibility and reputation on brand performance. Methods of quantitative description are used in this study. The present study employed purposive sampling, whereby the participants were selected based on their knowledge of and experience with purchasing iPhone brand products within the purchase range of March 2023 - March 2024. In all, 104 people took part in this study. Version 3.3.9 of the Smart PLS analysis program is used to process partial least squares, which are utilized in data analysis in research. Respondents were given a Google Form questionnaire with a scale from 1 to 4 that included the options for strongly disagree, disagree, agree, and highly agree. The study's findings demonstrate how brand credibility affects brand performance. Then, brand performance is influenced by brand reputation. The author's managerial inference is that buyers often second-guess their decision to purchase a product at a high cost. Because people, especially in Indonesia, continue to cite the rule of demand, which states that buyers would purchase a comparable good at a lower cost if the price of one product is higher than another. Secondly, the straightforwardness of finding iPhone products in stores should not be taken into account when making a direct purchase. Customers will take selling price and features into perspective.